Teaching Strategy to Develop the Skill of Certifying Death in Medicine Students - Josefa Caridad de la Rosa Chaviano; Eloy Arteaga Valdés; Olga Castellanos Morales; Bladimir Arteaga Valdés; Leslie Carcassés de la Rosa (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2012)
One of the most serious issues higher education faces today is the current inconsistency between the level of requirements and development of skills in future professionals training. Research has proved that there are difficulties in medicine students when developing the skill of certifying death. Therefore, we propose the following objective: to develop a teaching strategy based on the psychopedagogical foundations of skills formation processes in order to develop the skill of certifying death in 5th year medicine students through the study of Legal Medicine and Medical Ethics subjects. Research methods were used at theoretical and empirical levels. Experts' consultations was conducted in order to assess the relevance and effectiveness of the teaching strategy. We concluded that the implementation of the strategy, including the formation of a generalized procedure as a basis to develop the ability of certifying death, provides a great potential to help developing that skill.